ИССЛЕДОВАНИЕ АВТОКОРРЕЛЯЦИОННЫХ ФУНКЦИЙ В ЭЛЕКТРИЧЕСКИХ ЦЕПЯХ С ИСПОЛЬЗОВАНИЕМ ПРЕОБРАЗОВАНИЯ В ОРИЕНТИРОВАННОМ БАЗИСЕ - Терещенко, Т.А.; Хижняк, Т.А.; Лайкова, Л.Г.; Пархоменко , А.С. (Інститут електродинаміки НАН України, Київ, 2016)
The method for fast calculation of the values of arithmetic autocorrelation functions (ACF) using the transformation in oriented basis is proposed for research of electrical circuits. Recurrent matrix forms calculated by the modeling of typical form of signal allowed simplify the calculation of such functions. The complexity of calculating of arithmetic ACF was compare for different transformations - fast Fourier transformation, Walsh transformation and transformation in oriented basis. References 6, figures 2.